AN ANALYSIS OF LIBRARY SERVICE QUALITY USING THE IMPORTANCE-PERFORMANCE ANALYSIS (IPA) METHOD - Rudamin, Rudamin; Kaharuddin, Kaharuddin; Mansyur, Mansyur (JURNAL EDUSCIENCE, 2025)
Purpose – This study aims to analyze the quality of library services at SMAN 9 Tana Toraja based on five dimensions: tangibles, reliability, responsiveness, assurance, and empathy.Methodology – This research employs a descriptive quantitative approach, utilizing the Importance-Performance Analysis (IPA) model. The study population consisted of 525 students who regularly use the library at SMAN 9 Tana Toraja, with a sample of 228 students determined using the Slovin formula. Data was collected through questionnaires distributed via Google Forms and analyzed using a Cartesian diagram to map performance against importance.Findings – The overall suitability level of library services was 83.086%, categorized as "fairly appropriate". The IPA matrix revealed that the empathy dimension is a top priority for improvement (Quadrant A). The reliability and assurance dimensions performed well and should be maintained (Quadrant B). Meanwhile, the tangible and responsiveness dimensions were identified as low priorities (Quadrant C). No attributes were found to be excessive (Quadrant D).Contribution – This research provides a theoretical foundation for evaluating library service quality in educational settings. It offers concrete, data-driven recommendations for SMAN 9 Tana Toraja to enhance its library services, thereby supporting student literacy and the overall educational process.